Legal Analysis of Judges' Considerations in Granting Marriage Dispensation and Vulnerability Factors for Early Divorce: A Case Study of Decision Number 106/Pdt.P/2025/PA.Smg - Anam, Choiril; Lailasari Ekaningsih; Idul Hanzah Alid; Abdul Aziz, Abdul Azim Muhamad Bin (Institut Agama Islam Negeri Kendari, 2026)
Marriage dispensation remains a significant issue in Indonesian family law following the enactment of Law Number 16 of 2019, which raised the minimum legal age for marriage to 19 years for both men and women. Despite this reform, courts continue to grant marriage dispensations, raising questions about judicial reasoning and the extent to which substantive child protection principles are applied. This study examines the judicial reasoning in Decision Number 106/Pdt.P/2025/PA.Smg, evaluates its compliance with the applicable legal framework, and identifies vulnerability factors that may affect the sustainability of early marriages. This research employed a normative juridical approach using statutory, conceptual, and case approaches. Legal materials were analyzed qualitatively through a descriptive-analytical method. The findings show that the Court complied with procedural requirements under Law Number 16 of 2019, Supreme Court Regulation (PERMA) Number 5 of 2019, and the Compilation of Islamic Law. However, procedural compliance was not accompanied by a comprehensive substantive assessment of the child's best interests, particularly regarding psychological readiness, educational continuity, economic capacity, reproductive health, and long-term welfare. The decision also reveals a cumulative vulnerability profile involving young age, limited educational attainment, economic vulnerability, and premarital pregnancy. These factors should be treated not as deterministic causes of marital instability but as indicators requiring prospective judicial assessment. Theoretically, this study proposes a procedural substantive dual layer model of judicial reasoning arguing that procedural compliance is necessary but insufficient for child-protective adjudication. It further conceptualizes the gap between procedural legality and substantive child protection as a judicial child-protection gap positioning cumulative vulnerability assessment as a mechanism for operationalizing the best-interests principle. Keywords: Early Divorce Vulnerability; Islamic Family Law; Judicial Reasoning; Marriage Dispensation; Substantive Child Protection.